(3GdaUhUs - (3UGYO Hf GdMSf Hf YjSi GdQHYj GdHZOGOj, CHh GdYdGA,J (B417 (3g` s ((3YHO Gddg Hf YeQ Hf YKeGf GdJQZi s)
(3ChdgG (B:s
(3Cbhd HYO MeO Gddg Ydi cd eG bVGg hGdJhNi dHdhY eG ajg QVGg s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3GdMeO ddg Kef cd fYeI hdG Edg EdG Gddg Kef GdLfI hef bGd eQg (B: (3dG Edg EdG Gddg PNd GdLfI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B186 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B318s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs